Food plants to stingless bee Trigona fulviventris (Guérin-Méneville) in Pocosol, Guanacaste, Costa Rica - Barrantes-Vásquez, Alejandra (2018)
In this study, the main important plants collected by the stingless bee Trigona fulviventris were determined in a secondary dry forest fragment in Pocosol, Guanacaste during the rainy season. A total of 26 pollen types were obtained by collecting individuals of Trigona fulviventris these corresponded mainly representative species of herbs and shrubs. In addition, although there was unusual phenology through the year of the study, a collection of plants was carried out in order to covering the most important species according within the flight range of this species (300-500 m). For the palinological analysis a combination of methods were used and the results showed a convergence of 27% of coincidence when comparing both pollen collected by the bees and plant sources. In addition, the presence of the most representative species at the time of study at the site (Baltimora recta and Dorstenia contrajerva) was determined using ecological indexes. Moreover it was able to demonstrate a generalist behavior of T. fulviventris regarding the search for limited nutritional.